2022
DOI: 10.1088/2515-7620/acab4f
|View full text |Cite
|
Sign up to set email alerts
|

Warming diminishes the stability of primary productivity in global grass- and forb-dominated ecosystems

Abstract: Global warming has induced increases in productivity in open, grass- and forb-dominated (OGFD) ecosystems. However, little attention has been given to the temporal stability of productivity responses to global warming. We show that the stability of productivity in OGFD ecosystems decreased significantly over the past 40 years. Using the satellite-derived normalized difference vegetation index (NDVI) data from the Global Inventory Modelling and Mapping Studies (GIMMS) group, we analyzed global patterns of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…4d), which were different from previous studies. Although some studies indicated that climate warming may reduce community stability (Gao et al, 2022;Liu et al, 2021), Liu et al (2021) found that the decrease in community stability is caused by the decrease in productivity due to increased water limitation by increase temperature. Therefore, the impact of temperature change on community stability likely depends on water constraints.…”
Section: Discussionmentioning
confidence: 99%
“…4d), which were different from previous studies. Although some studies indicated that climate warming may reduce community stability (Gao et al, 2022;Liu et al, 2021), Liu et al (2021) found that the decrease in community stability is caused by the decrease in productivity due to increased water limitation by increase temperature. Therefore, the impact of temperature change on community stability likely depends on water constraints.…”
Section: Discussionmentioning
confidence: 99%